UNUSUAL SURGERY FOR A HEPATOCARCINOMA DISGUISED AS AN ADENOMA. (4th January 2023) - Perra, T; Porcu, A
Abstract: Introduction: Hepatic neoformations should always be adequately evaluated, even if they are suspected of being benign. We present a case of suspected hepatic adenoma that turned out to be hepatocarcinoma. Clinical case: A 38-year-old woman was admitted to the general surgery clinic due to the ultrasound finding of a hepatic neoplasm. Preoperative imaging tests and biopsy led to a diagnosis of hepatic adenoma. An abdominal CT scan showed a polylobulated expansive lesion occupying almost completely hepatic segments 5, 6 and 8 (11 cm) and an additional lesion in S8 (15 mm). The main lesion was in contact with the right hepatic vein, the middle hepatic vein, the retrohepatic vena cava, and the portal vein bifurcation. Surgical exeresis of the neoformation was performed. The surgical approach required subluxation of the liver to get direct control of the veins, rather than proceeding in an anteroposterior direction. The pathological anatomy of the mass was compatible with hepatocellular carcinoma with a solid-trabecular growth pattern and clear cell features. The heterogeneous pattern of neoplastic differentiation was indicative of a hepatocarcinoma developed on a previous adenoma. Discussion: This case illustrates the challenges that can arise in the diagnosis of hepatocarcinoma. A correct definition and analysis of all the available elements are essential in planning the surgical treatment of liver tumors.